1998
DOI: 10.1007/bf02550229
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of ejaculatory duct obstruction

Abstract: A total of 191 patients were evaluated at our department for azoospermia, and 11 were found to have azoospermia due to ejaculatory duct obstruction as proved by normal serum hormones, normal testicular biopsy, low ejaculate volume and absence of fructose in semen. Also transrectal ultrasound was performed, revealing distended seminal vesicles and dilated ejaculatory ducts. All these criteria together suggested ejaculatory duct obstruction as a cause of azoospermia. All patients underwent endoscopic management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It has been also shown that transrectal vesiculography and retrograde opacification could be performed to assess the normal patency of the vas deferens [36,37], but this can only be done immediately prior to endoscopic resection. Selection of patients with an isolated EDO, without combined proximal obstruction, would probably improve results of transurethral resection of the ED, which restores a normal sperm count in only 20±60 % of azoospermic patients [38,39,40,41,42,43,44] Mega-VS and functional causes of ejaculatory duct obstruction. Mega-VS and functional causes of ejaculatory duct obstruction (EDO) are far rarer [30] The obstruction is due to a disorder of seminal vesicle contraction.…”
Section: Ejaculatory Duct Obstructionmentioning
confidence: 98%
“…It has been also shown that transrectal vesiculography and retrograde opacification could be performed to assess the normal patency of the vas deferens [36,37], but this can only be done immediately prior to endoscopic resection. Selection of patients with an isolated EDO, without combined proximal obstruction, would probably improve results of transurethral resection of the ED, which restores a normal sperm count in only 20±60 % of azoospermic patients [38,39,40,41,42,43,44] Mega-VS and functional causes of ejaculatory duct obstruction. Mega-VS and functional causes of ejaculatory duct obstruction (EDO) are far rarer [30] The obstruction is due to a disorder of seminal vesicle contraction.…”
Section: Ejaculatory Duct Obstructionmentioning
confidence: 98%
“…However, despite technological advances in urologic equipment, endoscopic catheterization of the ejaculatory ducts was not widely used for various reasons: first of all it was difficult to perform, due to the location of the orifices of the ducts, in the posterolateral portion of the seminal colliculus (Veru Montanum) and the fragility of the ducts themselves. It also carried the risk of ascendant infections [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…Based on larger studies, TURED appears to lead to a 12.5%-31% spontaneous pregnancy rate depending on the etiology of EDO (2,10,(27)(28)(29)(30)(31)(32). In general, outcomes include improved semen parameters in 63%-83% of patients in general, or in 59% of patients with complete EDO and in 94% with partial EDO (2,11,(27)(28)(29). More specifically, 90.5% may have an increased semen volume (32), 50% of patients may have improvement in sperm count (10), and 60.5% may convert from azoospermia to having sperm in their ejaculate.…”
Section: Transurethral Resection Of Ejaculatory Ductmentioning
confidence: 99%
“…Some papers do not report complications or deny any complications from TURED (23,30). However, complication rates have been reported from 4%-26% (2,11,27,28,31,32,35).…”
Section: Transurethral Resection Of Ejaculatory Ductmentioning
confidence: 99%
See 1 more Smart Citation